BAURAN PEMASARAN (MARKETING MIX) KONVENSIONAL DAN DIGITAL DARI PEDAGANG PAKAIAN PASAR PONCOL JAKARTA PUSAT PADA MASA PANDEMI COVID-19 - Nofitra, Muhammad Ilham; Manggabarani, Alfatih S.; Astuti, Miguna (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023DO - 10.24843/EEB.2023.v12.i02.p05, 2023)
This study aims to identify and analyze the conventional and digital marketing mix of clothing traders at Poncol Market, Central Jakarta during the Covid 19 pandemic. A qualitative research approach using data collection techniques with in-depth interviews, documentation, and observation. Data validation techniques use triangulation of sources, techniques, and theories. Procedural data analysis techniques use interactive models from Miles et al (2016). This study aims to identify and analyze the conventional and digital marketing mix of clothing vendors at the Poncol Market, Central Jakarta during the Covid-19 pandemic. A qualitative research approach using data collection techniques with in-depth interviews, documentation, and observation. The results of the study show that traditional or conventional marketing appears to have advantages in product quality and variety, cheaper prices as well as advantages in terms of people and processes (such as free delivery to the Jakarta area). The downside is from the location aspect, access to markets is increasingly limited. Likewise, their promotions are still not optimal.